Low body mass index in long standing rheumatoid arthritis: relation to RA disease activity and functional indices - S.M. Gamal; A.K. Alkemary; M.A. Abdo; A.H.M. El Dakrony (PAGEPress Publications, 2018)
The aim of the work was to study the relationship between the body mass index (BMI) in longstanding rheumatoid arthritis (RA) and RA disease activity and functional indices. This study included 105 RA patients. For all patients, we recorded the presence of erosions on radiographs, the presence of subcutaneous nodules (SCN), the 28-tender joint count (TJC), 28-swollen joint count (SJC) scores, the visual analogue scale (VAS), physicians' global assessments (PhGA), the erythrocyte sedimentation rate (ESR), and the rheumatoid factor (RF). The disease activity index (DAS28) and BMI were calculated and current treatment was recorded. Patients were divided into two groups: group I: BMI 25. Group I included 32 (30.5%) patients, whereas group II included 73 (69.5%) patients. There were statistically significant differences between the two groups regarding each of the following: SJC (p=0.006), erosions (p=0.006), DAS28 (p=0.016) and PhGA (p=0.007). All were higher in group I (underweight and normal) than in group II (overweight and obese). No statistically significant differences emerged regarding age (p=0.11), smoking (p=0.69), disease duration (p=0.46), TJC (p=0.14), SCN (p=1.00), HAQ (p=0.26), VAS (p=0.16), ESR (p=0.25), RF (p=0.54) and steroid cumulative dose (p=0.08). Low BMI in longstanding RA patients may indicate more active and erosive disease and it may be considered as a poor prognostic factor.